2015
DOI: 10.1371/journal.pone.0116399
|View full text |Cite
|
Sign up to set email alerts
|

Diguanylate Cyclase Null Mutant Reveals That C-Di-GMP Pathway Regulates the Motility and Adherence of the Extremophile Bacterium Acidithiobacillus caldus

Abstract: An understanding of biofilm formation is relevant to the design of biological strategies to improve the efficiency of the bioleaching process and to prevent environmental damages caused by acid mine/rock drainage. For this reason, our laboratory is focused on the characterization of the molecular mechanisms involved in biofilm formation in different biomining bacteria. In many bacteria, the intracellular levels of c-di-GMP molecules regulate the transition from the motile planktonic state to sessile community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 85 publications
2
35
0
1
Order By: Relevance
“…These mainly include: (i) induction of the genes encoding the F0-ATPase subunit leading to the PMF allowing AHL efflux and influx, (ii) repression of several genes involved in carbohydrate metabolism to orientate carbon flow to maltodextrin and EPS building block precursor synthesis for adhesion and biofilm formation, respectively; (iii) induction of phosphate and ammonium transporters to anticipate inorganic ion gradient within and around the biofilm structure. Whereas QS and c-di-GMP pathway have been linked in different bacterial species ( Waters et al, 2008 ; Zhang, 2010 ; Kozlova et al, 2011 ; Suppiger et al, 2016 ), it is noteworthy that no change in the transcriptional profiling of the seven genes related to the c-di-GMP pathway in A. ferrooxidans ( Ruiz et al, 2012 ; Castro et al, 2015 ) has been observed in the presence of tetrazole 9c. This result indicates that QS does not modulate c-di-GMP signaling in this Gram-negative species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These mainly include: (i) induction of the genes encoding the F0-ATPase subunit leading to the PMF allowing AHL efflux and influx, (ii) repression of several genes involved in carbohydrate metabolism to orientate carbon flow to maltodextrin and EPS building block precursor synthesis for adhesion and biofilm formation, respectively; (iii) induction of phosphate and ammonium transporters to anticipate inorganic ion gradient within and around the biofilm structure. Whereas QS and c-di-GMP pathway have been linked in different bacterial species ( Waters et al, 2008 ; Zhang, 2010 ; Kozlova et al, 2011 ; Suppiger et al, 2016 ), it is noteworthy that no change in the transcriptional profiling of the seven genes related to the c-di-GMP pathway in A. ferrooxidans ( Ruiz et al, 2012 ; Castro et al, 2015 ) has been observed in the presence of tetrazole 9c. This result indicates that QS does not modulate c-di-GMP signaling in this Gram-negative species.…”
Section: Discussionmentioning
confidence: 98%
“…Even if several reports related to biofilm formation regulation by acidophilic bacteria belonging to Acidithiobacillus genus have been released recently ( Farah et al, 2005 ; Bellenberg et al, 2012 , 2014 ; Ruiz et al, 2012 ; Diaz et al, 2013 ; Montgomery et al, 2013 ; Vera et al, 2013 ; Castro et al, 2015 ), the molecular cascade involved in exopolysaccharide production and biofilm formation by Acidithiobacillus species is still undeciphered. While c-di-GMP pathway has been identified in all Acidithiobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ferrooxidans and A. ferrooxidans possess chemotaxis systems for sensing Fe(II), which might function to identify specific sites on pyrite surfaces for attachment [308,309]. Quorum sensing functions in bioleaching bacterium allow for swarming behavior on metal sulfides and play a key role in biofilm formation, enhancing dissolution of the mineral substrate [310][311][312][313][314][315]. Early biofilm formation involves capsular polysaccharide production (CPS), up-regulation of genes related to pili and EPS production, motility and quorum sensing, synthesis of cell wall structures, specific proteases, stress response chaperons, and mixed acid fermentation [316][317][318][319].…”
Section: Attachment Of Extreme Thermoacidophiles To Surfacesmentioning
confidence: 99%
“…For scanning electron microscopy, cells were grown in basal salts/trace elements medium (Ñancucheo et al 2016) containing sulfur as sole electron donor at 30 °C. Sulfur coupons were prepared as described by Castro et al (2015). Samples were critical point dried, coated with gold and observed with a LEO 1420VP scanning electron microscope.…”
Section: Phenotype and Chemotaxonomy Observationsmentioning
confidence: 99%